Red Blood Cell Homeostasis: Pharmacological Interventions to Explore Biochemical, Morphological and Mechanical Properties - Cluitmans, Judith C. A.; Gevi, Federica; Siciliano, Angela; Matte, Alessandro; Leal, Joames K. F.; De Franceschi, Lucia; Zolla, Lello; Brock, Roland; Adjobo-Hermans, Merel J. W.; Bosman, Giel J. G. C. M. (Frontiers in Molecular Biosciences, 2016)
During their passage through the circulation, red blood cells (RBCs) encounter severe physiological conditions consisting of mechanical stress, oxidative damage and fast changes in ionic and osmotic conditions. In order to survive for 120 days, RBCs adapt to their surroundings by subtle regulation of membrane organization and metabolism. RBC homeostasis depends on interactions between the integral membrane protein band 3 with other membrane and cytoskeletal proteins, and with key enzymes of various metabolic pathways. These interactions are regulated by the binding of deoxyhemoglobin to band 3, and by a signaling network revolving around Lyn kinase and Src family kinase-mediated phosphorylation of band 3. Here we show that manipulation of the interaction between the lipid bilayer and the cytoskeleton, using various pharmacological agents that interfere with protein-protein interactions and membrane lipid organization, has various effects on: (1) morphology, as shown by high resolution microscopy and quantitative image analysis; (2) organization of membrane proteins, as indicated by immunofluorescence confocal microscopy and quantitative as well as qualitative analysis of vesicle generation; (3) membrane lipid organization, as indicated by flow cytometric analysis of phosphatidylserine exposure; (4) deformability, as assessed in capillary-mimicking circumstances using a microfluidics system; (5) deformability as determined using a spleen-mimicking device; (6) metabolic activity as indicated by metabolomics. Our data show that there is a complex relationship between red cell morphology, membrane organization and deformability. Also, our data show that red blood cells have a relatively high resistance to disturbance of membrane organization in vitro, which may reflect their capacity to withstand mechanical, oxidative and osmotic stress in vivo.